Effectiveness of the Use of Information Technologies in Fulfilling Creative Tasks in Primary School Mathematics - Jonpolatovna, Saidova Mokhinur; Gulomovna, Ubaydullayeva Sharofat (European Journal of Life Safety and Stability (2660-9630), 2021)
This article discusses the topic of working on creative assignments using information technology in elementary school math classes. The types of assignments that develop students ’thinking are revealed. The effectiveness of such tasks in the student’s activity, in particular, the development of abilities and thinking, is reflected.